2022
DOI: 10.1186/s12893-021-01441-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a novel virtual reality simulation system with the focus on training for surgical dissection during laparoscopic sigmoid colectomy

Abstract: Background Mastery of technical skills is one of the fundamental goals of surgical training for novices. Meanwhile, performing laparoscopic procedures requires exceptional surgical skills compared to open surgery. However, it is often difficult for trainees to learn through observation and practice only. Virtual reality (VR)-based surgical simulation is expanding and rapidly advancing. A major obstacle for laparoscopic trainees is the difficulty of well-performed dissection. Therefore, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…When comparing the scores of the VR group and the lecture group, there was no difference between the pre-test total scores (7 [5][6][7][8][9] vs 6 [5-7.5], P=.352). However, the VR group had significantly higher post-test total scores than the lecture group (12 [9.5-12] vs 9 [8][9][10][11][12], P=.024), Table 2, Fig 2A . In the category-based sub-analysis, the post-test scores of aprons and gloves tended to be higher in the VR group, but the differences were not significant (P=.076 and P=.052, respectively; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing the scores of the VR group and the lecture group, there was no difference between the pre-test total scores (7 [5][6][7][8][9] vs 6 [5-7.5], P=.352). However, the VR group had significantly higher post-test total scores than the lecture group (12 [9.5-12] vs 9 [8][9][10][11][12], P=.024), Table 2, Fig 2A . In the category-based sub-analysis, the post-test scores of aprons and gloves tended to be higher in the VR group, but the differences were not significant (P=.076 and P=.052, respectively; Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Contrastly, previous reports have shown the effectiveness of VR in educating on practical skills such as surgical and endoscopic techniques and emergency room triage. 8,9,11 We believe the strength of VR is that it is suitable for acquiring practical skills as well as knowledge through scenario-based immersive experiences. 6,7 However, the limitations of VR are that it requires considerable time, effort, and high cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VR allows for the creation of realistic, interactive environments that can be used to train surgeons and other medical professionals, as well as to test new procedures and devices. Other research has shown that VR can be an effective tool for teaching surgical skills and for training healthcare professionals in laparoscopic surgery (Aoki et al, 2020; Gleason et al, 2022; Kamat et al, 2022; Mori et al, 2022; Yu et al, 2022) and neurosurgery (Petrone et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a VR simulation system, Lap-PASS LP-100 (Mitsubishi Precision Co., Ltd, Tokyo, Japan) [53], focuses on training to create proper tension on the tissue in laparoscopic sigmoid colectomy dissection (Figure 3) [54]. This system was validated by asking 44 surgeons (ranging from expert to novice) and six non-medical professionals to carry out a medial dissection of the sigmoid mesocolon on the simulator.…”
Section: Left-sided Colectomymentioning
confidence: 99%